Influence of the Socratic method on the reflection of the students of the National College of Application UNHEVAL-2022 - Vela-Lastra, Roberto (2023)
The present investigation entitled: Influence of the Socratic method on the reflection of the students of the National College Application UNHEVAL-2022, had the objective of determining the influence of the Socratic method on the reflection of the students of the 4th grade of secondary school of said educational institution. The research method used was the quasi-experimental design, where we worked with an experimental group of 32 students and a control group of 30, from sections "A" and "B" respectively; For data collection, a team applied as pre and post test was used, said instrument was validated by experts and went through Cronbach's alpha test for greater reliability. The results show that after the application of the Socratic method, 94% reached the level of reflection Achieved and only 6% remained at the Process level, compared to the initial results that showed 63% Achieved and 38% Process, which means that 32% of students in the 4th grade "A" went from the Process to the